Use of seven types of medical jargon by male and female primary care providers at a university health center. Issue 5 (May 2022) - Miller, Ann Neville; Bharathan, Ajay; Duvuuri, Venkata Naga Sreelalitapriya; Navas, Vanessa; Luceno, Lisvet; Zraick, Richard; Atmakuri, Shreya; Schmidt-Owens, Mary; Deichen, Michael; Ayers, Teresa; Thrash, Kimberley
Highlights: On average, providers used just over four jargon terms per visit. Just under half of distinct jargon terms were explained, with 78.16% of appointments including at least one instance of unexplained jargon. The most frequently used types of jargon were technical terminology and medical vernacular. Male providers used nearly 50% more jargon per minute, and more technical terminology, than female providers. Abstract: Objectives: The purposes of this study were to investigate extent and type of jargon use among primary care providers at a university health center, to evaluate the association of jargon use with patient outcomes, and to identify differences in jargon use between male and female providers. Method: The study employed a causal comparative design. Audio recordings of 87 primary care interviews were transcribed and coded using Pitt and Hendrickson's seven-category medical jargon classification framework. Results: Nearly 80% of appointments included at least one instance of unexplained jargon, with an average of more than four uses of jargon per visit. The most frequently used types of jargon were technical terminology and medical vernacular. Acronyms and abbreviations, medicalized English, and unnecessary synonyms were also regularly used. Just under half of distinct jargon terms were explained. Male providers used nearly 50% more jargon per minute than female providers, and they used more technical jargon than did their female colleagues. However, they explained that jargon just as frequently as female providers. Conclusions: Whereas previous studies have frequently limited the operational definition of jargon to two or three types, the comprehensive typology proposed by Pitt and Hendrickson provides a useful tool for identifying a wide range of jargon usage. Future research should examine the outcomes of this range of jargon types in more varied, less educated patient populations, and across different types of healthcare providers. Practice implications: With jargon used on average more than once every four minutes in our sample, and only half of jargon terms explained, medical jargon may be more of a problem even in primary care contexts than providers themselves realize. Male providers especially may want to make efforts to become more conscious of their jargon use and take care to explain terms, in an effort to facilitate more effective patient-provider communication and improved patient outcomes.